Toll-like Receptor-Dependent Negative Effects of Opioids: A Battle between Analgesia and Hyperalgesia - Shah, Masaud; Choi, Sangdun (Frontiers in Immunology, 2017)
Our understanding of the pathophysiology of the pathological pain and the pharmacology of analgesic treatments has progressed tremendously over the past two decades. Among the well-documented pro-algesic factors, glia and other Toll-like receptors (TLRs)-expressing cells in the neuroimmune interface have been recognized for their role in the development of neuropathic pain and for compromising the analgesic effects of opioids. Here, we comprehensively review the molecular mechanisms of pain initiation and progression, the role of TLRs in these processes, and the molecular mechanisms of morphine and morphine-3-glucuronide (M3G) in TLR-dependent central immune signaling. The data reviewed here suggest that while targeting glia to treat neuropathic pain, both analgesic and analgesia-opposing effects of opioids must be considered by acknowledging their role in TLR-mediated signaling.